Karakteristik Anak Didik sebagai Dasar dalam Mendukung Proses Pendidikan Anak Usia Dini - Marsya Cikita; Herlisna Kuku; Meriyani Anggowa; Tri Sela Lauding (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2024)
Early Childhood Education (PAUD) is a crucial stage in shaping children's character and personality. This study aims to identify the characteristics of early childhood and analyze the role of teachers in supporting children's character development through an observational approach. The research method used is descriptive qualitative with direct observation techniques in one of the Kindergartens in Gorontalo City. The results of the observation show that early childhood has unique characteristics, such as spontaneity, high curiosity, and egocentric tendencies. However, challenges were also found in character development, such as lack of independence and unstable emotions. Teachers have a strategic role in overcoming these challenges through an individual approach, effective communication, and the creation of a conducive learning environment. The strategies implemented include providing examples of positive behavior, routine habits, and play activities that support children's character development. This study emphasizes the importance of a deep understanding of the characteristics of early childhood by educators to create an effective and enjoyable learning process, as well as to shape children's characters who are independent and emotionally stable.